Analisis Implementasi Kebijakan Dokter Spesialis Jaga On Site Di Instalasi Gawat Darurat Rumah Sakit Dr. Mohammad Hoesin Palembang - Anhar, Kms (UI Scholars Hub, 2015)
Since the introduction of the National Health Insurance Program January 1, 2014 has been an increase in patients visit to hospital-government hospitals. Emergency Department (ED) Hospital is a unit leader in the provision of hospital services. The increasing amount of patients visit especially in dr. Moh. Hoesin Palembang (RSMH) raises complex issues which experienced by other hospitals both at world, national and regional. Although the problems in the ED is complex they still expected to provide a certifiable quality service in accordance with the Decree of the Minister of Health no. 856 in 2009 about ED service standards. The problems in the ED RSMH Palembang since the issuance of Managing Director SK Number: KP.04.02 / II / 168/2014 About Staffing Medical Functional Specialists as Specialit Doctor On site is still encountered in the ED patient is still a long process of assessment, compliance specialist doctors still keep on site less so still found a long period of hospitalization is still high. The research aims to find out how to keep the policy implementation specialists doctors on site have been conducted in Palembang RSMH ED with George Edward III implementation model with variable resources (human resourches, budgeting, facilities, information and authority), communication (transmission, clarity, consistency), disposition (attitude implementers, incentives) and bureaucratic structure (SPO, fragmentation). The study was done with qualitative method through in-depth interviews to informants, secondary data and direct observation. Informants are the specialist doctors and the management of the hospital. Results of the analysis of research data obtained in case of policy implementation specialists on site have not been going well, due to the communication factor, disposition and organizational structure has not been going well and much needed resource support. The given proposal is the addition of appropriate power and competence standards, the revised SOP, provision of communication media, improvement of facilities, improving the coordination and monitoring functions regularly, advocacy to the head of the Indonesian health minister.